2015
DOI: 10.1016/j.meegid.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Hokkaido genotype of Puumala virus in the grey red-backed vole ( Myodes rufocanus ) and northern red-backed vole ( Myodes rutilus ) in Siberia

Abstract: Three species of Myodes voles known to harbor hantaviruses include the bank vole (Myodes glareolus), which serves as the reservoir host of Puumala virus (PUUV), the prototype arvicolid rodent-borne hantavirus causing hemorrhagic fever with renal syndrome (HFRS) in Europe, and the grey red-backed vole (M. rufocanus) and royal vole (M. regulus) which carry two PUUV-like hantaviruses, designated Hokkaido virus (HOKV) and Muju virus (MUJV), respectively. To ascertain the hantavirus harbored by the northern red-bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…For example, geographic-specific genetic variants have been reported for Puumala virus in the bank vole (Myodes glareolus) (Garanina et al 2009), Tula virus in the European common vole (Microtus arvalis) (Song et al 2004), and Andes virus in the colilargo (Oligoryzomys longicaudus) (Torres-Perez et al 2011). Both Muju virus in the royal vole (Myodes regulus) (Lee et al 2014) and Hokkaido virus in the grey red-backed vole (Myodes rufocanus) and northern red-backed vole (Myodes rutilus) (Yashina et al 2015) may represent genotypes of Puumala virus. These examples point to the urgency of studying the phylogeographic variation of viruses and their hosts to provide an essential foundation for understanding their evolutionary histories and as a prelude to forecasting their future emergence under changing environmental conditions (Hope et al 2013, Campbell et al 2015.…”
Section: Resultsmentioning
confidence: 99%
“…For example, geographic-specific genetic variants have been reported for Puumala virus in the bank vole (Myodes glareolus) (Garanina et al 2009), Tula virus in the European common vole (Microtus arvalis) (Song et al 2004), and Andes virus in the colilargo (Oligoryzomys longicaudus) (Torres-Perez et al 2011). Both Muju virus in the royal vole (Myodes regulus) (Lee et al 2014) and Hokkaido virus in the grey red-backed vole (Myodes rufocanus) and northern red-backed vole (Myodes rutilus) (Yashina et al 2015) may represent genotypes of Puumala virus. These examples point to the urgency of studying the phylogeographic variation of viruses and their hosts to provide an essential foundation for understanding their evolutionary histories and as a prelude to forecasting their future emergence under changing environmental conditions (Hope et al 2013, Campbell et al 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, two distinct genetic lineages of PUUV were identified circulating within the bank vole populations in Russia. “Russia” (RUS) genetic lineage includes strains from the Samara region, Bashkiria, Udmurtia, and Tatarstan (Plyusnin et al, 1994; Lundkvist et al, 1997; Kariwa et al, 2009), and “Finland” (FIN) genetic lineage includes strains from Karelia and western Siberia (Asikainen et al, 2000; Dekonenko et al, 2003; Yashina et al, 2015). Between these two lineages, S-segment nucleotide sequences diversity reaches over 15% (Razzauti et al, 2012), while within a local rodent population, nucleotide sequence diversity does not exceed several percent within one lineage (Avsic-Zupanc et al, 2007; Kariwa et al, 2009; Razzauti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Russia, many cases of HFRS are registered in the Volga region (Bashkiria, Udmurtia, and Tatarstan), the southern part of Siberia (Omsk, Tyumen, and Novosibirsk), and the Far East region (Amursky, Primorsky, and Khabarovsky regions) [63]. PUUV is the most commonly identified orthohantavirus causing HFRS in these areas, while only sporadic infections exist for DOBV [14,25,64]. Usually, each orthohantavirus is associated with specific natural host rodent and their geographical location [65][66][67] (Table 2, also see Figure 4).…”
Section: Distribution Of Orthohantaviruses and The Diseases They Causementioning
confidence: 99%
“…Currently, eight PUUV genetic lineages are identified in the bank voles: Central European (CE), Alpe-Adrian (ALAD), Danish (DAN), South Scandinavian (S-SCAN), North Scandinavian (N-SCAN), Finnish (FIN), Russian (RUS) and the newly identified Latvian (LAT) [18][19][20][21][22][23] (Table 1). It was demonstrated that the nucleotide genetic diversity between PUUV lineages for the S (small) segment is 15-19% [24,25], while the differences in nucleotide sequences between PUUV strains within the same lineage could range from 0 to 9% [20,26]. [18,22] The PUUV genetic diversity results from both the accumulation of the point mutations and rearrangement within the viral genome, such as recombination and reassortment [23,30].…”
Section: Introductionmentioning
confidence: 99%